Reviewing putative industrial triggering in pemphigus: cluster of pemphigus in the area near the wastewater treatment plant - Pietkiewicz, Paweł; Gornowicz-Porowska, Justyna; Bartkiewicz, Paweł; Bowszyc-Dmochowska, Monika; Dmochowski, Marian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
A range of pemphigus is relatively rare potentially fatal group of autoimmune blistering dermatoses. Usually, there is no apparent triggering, while in some predisposed patients there are alleged environmental/industrial inducing factors. In a short time period (4 years), we diagnosed 3 novel cases of pemphigus (1 pemphigus vulgaris, 1 pemphigus foliaceus and 1 shift from pemphigus foliaceus into pemphigus vulgaris) at a clinical and laboratory level (ELISA, immunofluorescence studies). We discuss a possible common inducing mechanism as these patients inhabit one estate of the Poznan suburbia (Kozieglowy, population < 12,000), Greater Poland district, Poland, and review literature data on alleged pemphigus triggers. To the best of our knowledge, this is the first report exploring the putative association between pemphigus diseases and wastewater treatment plant waterborne or volatile by-products in the vicinity of such a facility.